PENGARUH KOMPENSASI FINANSIAL, KEPEMIMPINAN PARTISIPATIF DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN PADA DYANA VILLAS, DI SEMINYAK - Setiawan, I Gede Yonatan Rudy; Sariyathi, Ni Ketut (E-Jurnal Manajemen, 2014)
The purpose of this study was to determine the effect of financial compensation, participative leadership and physical work environment on employee performance at Dyana Villas in Seminyak. This study used a qualitative research using surveys and questionnaires to 46 respondents. It was found that there is positive and significant variables simultaneously between financial compensation, participative leadership and physical work environment on employee performance at Dyana Villas in Seminyak. The next results show that there is positive and significant partial compensation between financial variables, participative leadership and physical work environment on employee performance at Dyana Villas in Seminyak. Physical working environment variable is a variable that is most dominant influence on the performance of employees at Dyana Villas in Seminyak
Keywords: Financial compensation, Participative Leadership, Physical Work Environment, Employee Performance